DOES THE INDEPENDENT BOARD OF COMMISSIONERS AFFECT TO SUSTAINABILITY REPORTS DISCLOSURE AND FINANCIAL PERFORMANCE - Putri Ratu Ayu Siahaan; Iqlima Azhar; Afrah Junita (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to determine the effect of economic performance, Environmental Performance, and Social Performance in the Sustainability Report on Financial Performance Provoked by ROA with the Board Independent Commissioner as a Moderation variable in Mining Companies. The research method used is a quantitative study with panel data and analyzed using Moderated Regression Analysis (MRA). The sample selection in this study was selected using the purposive sampling method so that a sample of 8 companies is obtained from mining companies listed on the Indonesia Stock Exchange (IDX). Data obtained was analyzed using Eviews 9. The results showed that partially the Economic Performance, Environmental Performance, and Social Performance contained in the sustainability report and The Independent Board of Commissioners has no significant effect on Performance Mining company finance. A partially Independent Board of Commissioners cannot moderate the effect of Economic Performance, Environmental Performance, and Social Performance in the Sustainability Report on the Company's Financial Performance mining. Simultaneously, the Independent Board of Commissioners can moderate the influence of Economic Performance, Environmental Performance, and Social Performance in the Sustainability Report on the Financial Performance of mining companies.